Neoliberal Globalization, Food Systems (Literacy) Transformation and Global Citizenship - Fuseini, I. (Reimagining Development Education in Africa, 2023)
This chapter discusses global citizenship as an imperative of development education, through the lens of food literacy. At the heart of development education is a transformative approach to pursuing human centred development by empowering people and communities through knowledge, values, attitudes, and skills. The notion of global citizenship is, persuasively, the moral anchor for the practice of development education. However, with the unfolding globalization forces, some of the qualities and values sometimes become contentious due to how they are produced, diffused and the potential negative implications about their outcomes. This leaves one to wonder whether to learn to get empowered to give effect to development education and global citizenship or to unlearn what is already known or is an accepted system of knowledge or values in order to promote the practice of development education. The chapter contributes to conceptualizing development education through global citizenship using food and nutrition literacy by focusing on the current processes of neoliberal globalization induced food system transformations, how the process creates unhealthy food environments and disrupts local food system knowledge, food literacy and skills, and how the individual reacts to such processes in terms of food and nutrition literacy, and aspirations for improved wellbeing. There is no doubt that globalization induced food system transformations have disrupted food literacy in some respects, principally due to availability of food in environments and cultures other than where the food was produced. Other dynamics such as food processing and preparation technologies, new ideas and sources of food literacy all interact to create a blurring effect of just what is useful food literacy, and which should be unlearned in order to achieve wellbeing. The chapter spotlights the tension between the known, locally relevant food literacy and that which is ‘imposed’ by neoliberal food systems transformation, and how this creates dissonance and convergence about food literacy as the individual joggles between wellbeing and being a global citizenship. The chapter argues that the homogenizing food literacy due to the effect of neoliberal globalization is antithesis to the concept of global citizenship as framed in development education, and concludes that the results are loss of relevant local food literacies, creation of unhealthy food environment and exposure of the population to poor health arising from increasing food-related non-communicable diseases (NCDs). It is recommended that multilevel governance and regulatory strategies, structures and frameworks be designed and implemented to counter the real and potential public health problems arising from the food systems transformation.These include legislative regulation on food component and nutritional information labelling, regulating ‘harmful’ food advertisement, creation of healthy food environment, prioritizing of recruitment of caterers with local food literacies to work in public sector as well as designing education campaigns to promote consumption of local foods by demystifying certain false claims about processed foods
Research Article
Keywords: Development education; Food security; Globalisation